(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
This article explores the psychological effects of different colored fabrics on human emotions and behavior. It delves into the scientific research surrounding the influence of colors such as red, blue, green, yellow, and black. Each color is analyzed in terms of its psychological impact, supported by relevant studies, and practical applications in various fields such as fashion, sportswear, workwear, medical attire, and interior design. The article provides insights into how the correct use of colored fabrics can enhance mood, productivity, and overall well-being